Care leavers' engagement with services: motivational factors which sustain a positive relationship - Marina Amaral (Scottish Journal of Residential Child Care)
According to Mitchell (1982), motivation refers to 'psychological processes that cause the arousal, direction and persistence of voluntary actions that are goal directed' (Mitchell 1982, p. 81). Thus, motivation is an individual process which might be influenced by extrinsic and intrinsic factors to the individuals. The former refers to the external factors experienced which make us self-determined to accomplish a certain task (for example, rewards such as money or a work promotion). The latter refers to the self-interest and enjoyment that a person experiences from doing an activity (for example, voluntary work).